Atmospheric Carbon Dioxide Removal: A Physical Science Perspective - Washington Taylor; Brad Marston; Robert Rosner; Jonathan Wurtele (PRX Energy)
Novel carbon dioxide removal (CDR) technologies are increasingly being considered as potentially useful tools to combat climate change. For specific atmospheric carbon dioxide management targets to be achieved, large-scale CDR strategies may be needed, even with aggressive efforts to reduce carbon dioxide emissions in the coming decades. This American Physical Society report breaks down the physical requirements necessary for large-scale implementation of CDR technologies, demonstrating the challenges inherent to incorporating CDR into any carbon dioxide management portfolio. It also provides a technical overview of new and current CDR approaches and evaluates their fundamental physical constraints. Based on the technical overview, the report makes several recommendations for the U.S. federal government and industry. These include ensuring that the potential for CDR does not compromise ongoing actions to reduce carbon emissions. The report observes, however, that while large-scale CDR technologies require a lot of energy and material resources, they might be needed in combination with emission reduction strategies to achieve specific climate goals. Research and development on CDR should be selectively pursued, despite the many challenges described in the report.